Hubungan Karakteristik Pasien Artritis Reumatoid dengan Derajat Depresi Berdasarkan Skor BDI-II - Nashya Nurghina Wilpi; Arina Widya Murni; Yaslinda Yaunin (Fakultas Kedokteran, Universitas Andalas, 2026)
Background: Depression is a mood disorder, most commonly associated with rheumatoid arthritis. The association of depression with rheumatoid arthritis is believed to be related to age, sex, socioeconomic factors, length of illness, and disease activity score. Objective: This study aims to determine the relationship between characteristics of rheumatoid arthritis patients with level of depression based on BDI-II scores. Methods: This study is an analytical research with a cross-sectional approach, using primary data taken through BDI-II questionnaire interviews. The study was conducted in December 2022 – February 2024 on rheumatoid arthritis patients at the Special Polyclinic of Rheumatology RSUP Dr. M. Djamil. The data obtained were analyzed using univariate and bivariate analysis with the chi-square test. Results: The results show that there is a significant relationship between age and degree of depression (p=0.038) and level of education with degree of depression (p=0.039). This study shows that there is no relationship between several patient characteristics and degree of depression (p>0.05) in rheumatoid arthritis patients at the Rheumatology Specialty Polyclinic of Dr. M. Djamil Hospital. Conclusion: The conclusion of this study is that there is a significant relationship between age and education level with degree of depression, but there is an absence of a significant relationship between gender, occupation, economic status, length of illness, and disease activity score with degree of depression based on BDI-II score.